2013
DOI: 10.1093/neuonc/not144
|View full text |Cite
|
Sign up to set email alerts
|

H3F3A K27M mutations in thalamic gliomas from young adult patients

Abstract: We found that high-grade thalamic gliomas from young adults, like those from children and adolescents, frequently had H3F3A K27M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
132
7
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 24 publications
17
132
7
2
Order By: Relevance
“…Highly recurrent mutations in genes that encode H3 histone proteins, which are involved in chromatin function and gene expression regulation, occur in about 38% of childhood and young adult (age ≤ 30 years) HGGs but are not seen in HGGs of older patients [4,10] . Conversely, IDH mutations, which are commonly found in adult gliomas, are extremely rare in children and essentially mutually exclusive with H3 histone mutations [8,9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly recurrent mutations in genes that encode H3 histone proteins, which are involved in chromatin function and gene expression regulation, occur in about 38% of childhood and young adult (age ≤ 30 years) HGGs but are not seen in HGGs of older patients [4,10] . Conversely, IDH mutations, which are commonly found in adult gliomas, are extremely rare in children and essentially mutually exclusive with H3 histone mutations [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to producing a mutant K27M form of histone H3 that can be detected by immunohistochemistry [12] , the alteration stimulates tumorigenesis via a multitude of changes that impact DNA transcription, replication, and repair [9,11] . HGGs with histone-encoding genes that harbor K27M mutations commonly arise in midline CNS structures and have been found in over 70% of diffuse gliomas originating from the brain stem, especially the pons, as well as in about half of gliomas arising in the spinal cord and thalamus [3][4][5][6] . A study by Solomon et al [1] that sought to characterize the anatomic locations and age range of DMG-K27Ms found that histone H3-K27M mutations were present in 64% of pediatric and adult diffuse gliomas involving midline structures, predominantly the brainstem, thalamus, and spinal cord, with few examples arising in the cerebellum, third ventricle, and hypothalamus.…”
Section: Color Version Available Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…34 Methylation of the methylguanine methyltransferase gene (MGMT) and p53 overexpression have been identified in a subset of high-grade infiltrating thalamic gliomas that, along with elevated proliferation, appear to correlate with particularly poor outcome. 33 Recently, H3K27M mutations have been detected in a significant subset (65%-90%) of high-grade pediatric and young adult thalamic DAs, 35,36 placing them firmly in the genetically defined category of diffuse midline glioma. These tumors are defined by the 1, 4, 6-9, 12, 13, 15, 18, 19, 31, 32.…”
Section: Diffuse Astrocytomamentioning
confidence: 99%
“…Furthermore, these different mutations also appear to segregate with distinct types of tumors. For instance, the K27M mutation has been found only in pediatric diffuse intrinsic pontine glioma (DIPG) and highgrade astrocytomas primarily restricted to midline locations (spinal cord, thalamus, pons, brainstem) in children and younger adults (11)(12)(13)(14)(15)(16)(17). The majority of K36M mutation has been found in chondroblastoma, and to a lesser extent, in clear-cell chondrosarcoma (9).…”
mentioning
confidence: 99%